PENCIPTAAN BUSANA GAYA ANDROGYNY DENGAN SUMBER IDE TARI JATHIL PADA KESENIAN REOG PONOROGO - Wahyu Laily, Prasidya; Nahari, Inty; Arifiana, Deny; Nashikhah, Ma’rifatun (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2025)
Indonesia has a rich culture that can be used as a source of inspiration in the creation of fashion designs, one of which is the Jathil dance in the Reog Ponorogo art form. The Jathil dance is unique because it represents a blend of masculinity and femininity. This is the primary foundation in the design of androgynous fashion, which harmoniously combines masculine and feminine elements. The purpose of this creation is to describe the process of creating androgynous-style fashion and to describe the presentation of androgynous-style fashion creation. The method used is practice-led research, which is a practice-based research approach through the stages of exploration, design, realisation, and presentation of the work. The creation process began with the development of alternative design sketches and alternative colour combinations. The results of this creation are three selected designs: one men's garment and two women's garments. The first work is a three-piece men's garment consisting of a top, bottom, and layered pants. The second work is a three-piece women's garment consisting of a tank top with a jathil silhouette appliqué and woven text, and a long skirt bottom. The third piece is a four-piece women's outfit consisting of a top, skirt, skirt layer, and ruffled sleeves. The presentation of this androgynous-style clothing creation is divided into three parts: pre-event, on-event, and post-event.